2020
DOI: 10.1007/s00348-020-03088-1
|View full text |Cite
|
Sign up to set email alerts
|

On the potential and challenges of laser-induced thermal acoustics for experimental investigation of macroscopic fluid phenomena

Abstract: Mixing and evaporation processes play an important role in fluid injection and disintegration. Laser-induced thermal acoustics (LITA) also known as laser-induced grating spectroscopy (LIGS) is a promising four-wave mixing technique capable to acquire speed of sound and transport properties of fluids. Since the signal intensity scales with pressure, LITA is effective in high-pressure environments. By analysing the frequency of LITA signals using a direct Fourier analysis, speed of sound data can be directly det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…A less complex non-linear technique that does not require fitting to a spectrally-resolved signal is laser-induced grating scattering (LIGS), also known as laser-induced thermal acoustics (LITA) [16][17][18]. LIGS/LITA experiments measure the speed of sound in a gas directly and models of the LIGS signal evolution can be used to determine transport properties such as the acoustic damping rate and thermal diffusivity, of key interest for studies of fundamental fluid physics [19]. Previous studies have demonstrated the capabilities of the LIGS technique for temperature measurements, which can readily achieve sub-1 % precision and accuracies of order 1 % [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A less complex non-linear technique that does not require fitting to a spectrally-resolved signal is laser-induced grating scattering (LIGS), also known as laser-induced thermal acoustics (LITA) [16][17][18]. LIGS/LITA experiments measure the speed of sound in a gas directly and models of the LIGS signal evolution can be used to determine transport properties such as the acoustic damping rate and thermal diffusivity, of key interest for studies of fundamental fluid physics [19]. Previous studies have demonstrated the capabilities of the LIGS technique for temperature measurements, which can readily achieve sub-1 % precision and accuracies of order 1 % [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous Raman scattering [2] and combined laser induced fluorescence and phosphorescence [36] enabled the measurement of gas composition in the wake of an evaporating droplet, gas temperatures and, for the case of acetone, mean droplet temperatures. Laser-induced thermal acoustics has been extended to enable the measurement of the acoustic damping rates in the supercritical region of pure fluids [56]. Based on these measurements, the importance of bulk viscosity in the liquid-like supercritical region was assessed and closure models for describing momentum transport and dissipation effects in supercritical fluids were evaluated.…”
Section: Transcritical Evaporation and Mixing Processesmentioning
confidence: 99%
“…A detailed description of the optical arrangement used for the presented investigations as well as the spatial resolution of approximately 312 mm in diameter and less than 2 mm in length in the x-direction can be found in the work of Steinhausen et al [28]. For a theoretical description of the generation of laser induced gratings the reader is referred to Cummings et al [4], Schlamp et al [26] as well as Stampanoni-Panariello et al [27].…”
Section: Laser Induced Thermal Acousticsmentioning
confidence: 99%
“…As descripted in our previous work [28] the evaluation of LITA signals proposed by Schlamp et al [26] enables us after careful calibration to extract the speed of sound c s , the acoustic damping rate as well as the thermal diffusivity D T from the shape of the LITA signal. Using the assumptions presented by Steinhausen et al [28] the time-dependent diffraction efficiency (t) of a detected LITA signal shows the following dependencies…”
Section: Lita Post-rocessingmentioning
confidence: 99%
See 1 more Smart Citation